Teaching ethics in a special graduation course: an experience of co-construction of knowledge - Enicéia Gonçalves MENDES (Aula, 2019)
Professional ethics is a topic that hardly appears prominently in the curricular matrices of teacher preparation courses in Brazil; however, if the later purpose of education is the formation of the person, it becomes important to incorporate the discussions about ethics in teacher education. The present report describes the experience of planning and teaching the Ethics discipline in a Special Education Degree course that aims to prepare the future teacher with the knowledge, skills and willingness to analyze situations and take decisions based on the ethics necessary to provide quality education for all students. The methodology was designed to promote the co-construction of knowledge, a process in which there are interactions between teachers and students and among the students themselves, resulting in collaborative knowledge construction. It is hoped that future teachers will be able to identify practices that promote self-development, and the development of the students of the Special Education, their families, other professionals and the profession of Special Education teacher.